Building Anti-Ableist Museum Education Practices: A Reflection and Facilitation Toolkit. (3rd April 2022) - Kon, Rebecca; Zankowicz, Kate
ABSTRACT: Building anti-ableist museum education practices into our toolboxes of educational skills is an important way to ensure that museum educators are dismantling the ableism at work in museum interpretation. This paper offers practical strategies for building anti-ableist museum education practices, which we model using one artwork, Enrique Martínez Celaya's sculpture The Gambler . These strategies include self-reflective practices for educators and facilitation strategies for use with program participants. We suggest these practices in a series of concrete activities based on self-reflection, dialogue and group experimentation with multiple points of view. These activities serve as tools to consider multiple points of view from disabled people and strategies for developing understandings of disability that counter ableist assumptions about disabled people's happiness, personal fulfillment, and quality of life – conversations that invariably arise when discussing the artistic representations of disabled people in museum collections.